2020
DOI: 10.3892/ijmm.2020.4783
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and anti‑inflammatory mechanisms of action of astaxanthin in cardiovascular diseases (Review)

Abstract: Cardiovascular diseases are the most common cause of mortality worldwide. Oxidative stress and inflammation are pathophysiological processes involved in the development of cardiovascular diseases; thus, anti-inflammatory and antioxidant agents that modulate redox balance have become research targets so as to evaluate their molecular mechanisms of action and therapeutic properties. Astaxanthin, a carotenoid of the xanthophyll group, has potent antioxidant properties due to its molecular structure and its arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 120 publications
1
62
0
4
Order By: Relevance
“…In the presence of oxidative stress, Nrf2 dissociates from Keap1, translocates into the nucleus, binds to the ARE, and induces the expression of Phase II enzymes, as shown in Figure 6 . Astaxanthin prevents lipid peroxidation by activating antioxidant enzymes involved in lipid metabolism, namely thioredoxin reductase (TrxR) and paraoxonase-1 [ 147 , 148 , 149 ]. Pongkan et al [ 150 ] depicted higher levels of mtROS production, mitochondrial depolarization, and swelling in mitochondria isolated from the ischemic myocardium of mice astaxanthin treatment decreases mtROS production, mitochondria depolarization, and swelling.…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%
“…In the presence of oxidative stress, Nrf2 dissociates from Keap1, translocates into the nucleus, binds to the ARE, and induces the expression of Phase II enzymes, as shown in Figure 6 . Astaxanthin prevents lipid peroxidation by activating antioxidant enzymes involved in lipid metabolism, namely thioredoxin reductase (TrxR) and paraoxonase-1 [ 147 , 148 , 149 ]. Pongkan et al [ 150 ] depicted higher levels of mtROS production, mitochondrial depolarization, and swelling in mitochondria isolated from the ischemic myocardium of mice astaxanthin treatment decreases mtROS production, mitochondria depolarization, and swelling.…”
Section: Microorganisms As a Source Of Antioxidant Compoundsmentioning
confidence: 99%
“…Astaxanthin, a carotenoid of the xanthophyll group, has important applications in the nutraceutical, cosmetics, food and feed industries [ 103 , 155 , 156 ]. Chemical structure of astaxanthin includes two oxygenated groups, hydroxyl and carbonyl, in each a ionone ring displays some unique properties such as more effective antioxidative activity and polar configuration as compared to other carotenoids [ 103 , 104 , 155 , 156 , 157 , 158 ]. Moreover, astaxanthin exerts some anti-inflammatory effects and modulates the lipid and glucose metabolisms [ 103 , 104 , 105 , 106 , 107 ].…”
Section: Molecules To Fight the Onset And Progression Of Cvdmentioning
confidence: 99%
“…Chemical structure of astaxanthin includes two oxygenated groups, hydroxyl and carbonyl, in each a ionone ring displays some unique properties such as more effective antioxidative activity and polar configuration as compared to other carotenoids [ 103 , 104 , 155 , 156 , 157 , 158 ]. Moreover, astaxanthin exerts some anti-inflammatory effects and modulates the lipid and glucose metabolisms [ 103 , 104 , 105 , 106 , 107 ]. In reason of these multiple pleiotropic effects, several studies have demonstrated that astaxanthin can delay the onset and progression of various CVD such as atherosclerosis, hypertension and dyslipidemia [ 103 , 104 , 105 , 106 , 107 , 159 , 160 , 161 , 162 ].…”
Section: Molecules To Fight the Onset And Progression Of Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…ASX has attracted interest due to its reported therapeutic effects in a range of health conditions [5]. This includes the prevention and treatment of cardiovascular diseases [2,[6][7][8], neurological diseases [9][10][11], ocular disorders [12,13], cancer [14] and improving dermal health [15,16]. ASX derived from the green microalga Haematococcus pluvialis is the main source for human applications including dietary supplements, cosmetics, and food.…”
Section: Introductionmentioning
confidence: 99%